2016
DOI: 10.3390/ijgi5090148
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Temporal Analysis Methods Using Residential Burglary Data

Abstract: Law enforcement agencies, as well as researchers rely on temporal analysis methods in many crime analyses, e.g., spatio-temporal analyses. A number of temporal analysis methods are being used, but a structured comparison in different configurations is yet to be done. This study aims to fill this research gap by comparing the accuracy of five existing, and one novel, temporal analysis methods in approximating offense times for residential burglaries that often lack precise time information. The temporal analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 22 publications
1
23
2
Order By: Relevance
“…So if an incident had a time span of 1:00 to 2:40, it would get a weight of 0.6 in the [1:00-1:59) bin, and a weight of 0.4 in the [2:00-2:59). Boldt and Borg (2016) refer to this as the Aoristic++ algorithm, but others were using this algorithm before they published that paper (see https://andrewpwheeler.wordpress.com/2013/01/30/aoristocratic-analysis-withspss/ for just one example). Additionally for my implementation, if a crime event spans longer than the entire temporal window, all bins are assigned equal weight.…”
Section: Example: Aoristic Analysis Of Within Day Burglary Patternsmentioning
confidence: 99%
“…So if an incident had a time span of 1:00 to 2:40, it would get a weight of 0.6 in the [1:00-1:59) bin, and a weight of 0.4 in the [2:00-2:59). Boldt and Borg (2016) refer to this as the Aoristic++ algorithm, but others were using this algorithm before they published that paper (see https://andrewpwheeler.wordpress.com/2013/01/30/aoristocratic-analysis-withspss/ for just one example). Additionally for my implementation, if a crime event spans longer than the entire temporal window, all bins are assigned equal weight.…”
Section: Example: Aoristic Analysis Of Within Day Burglary Patternsmentioning
confidence: 99%
“…It was concluded that the aoristic method best manages to estimate the offense time in that context. Which was supported when investigating residential burglaries [14].…”
Section: Related Workmentioning
confidence: 99%
“…Therefore, law enforcement agencies, as well as researchers, rely on temporal approximation methods in crime analysis. Several temporal approximation methods have recently been discussed in research (e.g., [ 1 , 9 – 12 ]). The choice of method of offense time approximation has a strong influence on results of (spatio)temporal analyses and a significant impact on law enforcement activities such as deploying resources and solving a particular case.…”
Section: Introductionmentioning
confidence: 99%